PROBLEMS OF HYDRAULIC CALCULATION OF EARTHEN CHANNELS - Khazratov, Alisher; Rakhmatov, Makhmud (Innovatsion texnologiyalar, 2024)
The main task of the design of earthen channels is to calculate the dimensions of the stable channel shape in which irreversible deformation of the channel cross-section does not occur. This article provides information on calculating the hydraulic parameters of a stable channel shape in the design of earthen channels in which channel deformation does not occur. In this case, the need to adopt dynamic stable channel parameters that can work in harmony with nature through the method of checking the dynamic stability of the channel with the help of hydraulic modeling programs is based on modeling using HEC-RAS software and field-experience data. Based on the research results, a new approach is required in the hydraulic calculation for the design of the earthen canals, taking into account the changing nature of the flow and discharge. Taking into account the natural increase of the bottom slope of the deformed channel bed due to sediment deposition, it is suggested to strengthen the side embankments of the channel and choose the flow slope that ensures the balance of the sediment balance. The essence of the proposed method consists in adopting dynamic stable channel parameters that are in harmony with nature and do not require continuous cleaning and repair works in the calculation of earthen channels. For this, it is necessary to model the sediment transport with the help of hydraulic modeling programs of the earthen channels.